TRANSFER PENGETAHUAN DAN KETERAMPILAN PEMOTONG KARET DI DESA BENGKOLAN SALAK, KECAMATAN PENDALIAN IV KOTO, KABUPATEN ROKAN HULU - Wulan Purnama; Daeng Ayub Natuna; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was motivated by the transfer of knowledge and skills ofrubber cutting, so the aim was to determine the transfer of knowledge and skills ofrubber cutting in Bengkolan Salak Village, Pendalian IV Koto District, Rokan HuluRegency, whether good or bad. This type of research is descriptive with a quantitativeapproach. The population in this study were 72 rubber cutters in Bengkolan SalakVillage, Pendalian IV Koto District, Rokan Hulu Regency. The technique used is SimpleRandom Sampling. After testing, the number of valid data is 42 and invalid data is 3.Then the invalid data lies at number 6 (0.253 <0.444), number 7 (0.175 <0.444), andnumber 19 (0.393 <0.444). All invalid items are discarded meaning they are not used inthe study, because all valid items represent indicators and sub indicators. In measuringresilience, meanwhile, valid items are used for field research because these items havebeen tested for the level of truth to measure resilience. Based on the results of theanalysis that has been described, the transfer of knowledge and skills of rubber cuttingin Bengkolan Salak Village, Pendalian IV Koto District, Rokan Hulu Regency obtaineda mean mean value of Mean 3.75 and SD 0.79 which are in a sufficiently interpretativeposition. high (good).Key Words: Transfer of Knowledge and Skills